Ectomycorrhizas naturally established in Nothofagus nervosa seedlings under different cultivation practices in a forest nursery - Fernandez, Natalia Verónica; Marchelli, Paula; Fontenla, Sonia Beatriz (Springer, 2018)
Mycorrhizas are mutualistic associations between soil fungi and plant roots which usually improve water and nutrient uptake, influencing plant fitness. Nothofagus nervosa (Raulí) is an ecologically and economically important species of South American temperate forests. Since this native tree species yields valuable timber, it was overexploited and its natural distribution area was critically reduced, so it is currently included in domestication and conservation programs. Among the factors that should be considered in these programs are the ectomycorrhizas (EcM), which would be important for the successful establishment and survival of outplanted seedlings. The aim of this work was to analyze the abundance and diversity of EcM in N. nervosa nursery-cultivated seedlings assessed by morphotyping, fungal isolation, and DNA sequencing. Arbuscular mycorrhiza (AM) occurrence was also studied. A 2-year trial was conducted following the cultivation conditions used for domestication programs. Seedlings were cultivated under two different cultivation practices (greenhouse and nursery soil) without artificial inoculation of mycorrhizal fungi. Seedlings’ roots were examined at different times. It was observed that they developed EcM between 6 and 12 months after germination and AMs were not detected in any plant. The most abundant ectomycorrhizal fungi present in seedlings’ roots were Tomentella ellisii (Basidiomycota) and an unidentified fungus named Ascomicetous EcM sp. 1. Abundance and diversity of EcM varied between the two cultivation techniques analyzed in this study, since seedlings that continued growing in the greenhouse had higher colonization values, but those transplanted to the nursery soil were colonized by a higher diversity of fungal taxa.